2004
DOI: 10.1007/s00464-003-9131-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-trocar adnexal surgery: a “quasi” scarless operation

Abstract: The use of a two-trocar technique is safe and highly appreciated by the patients it leaves no visible abdominal scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…24 In laparoscopy, reduction of surgical trauma is achieved through a decrease either in the number or size of portals. 25,26 To reduce the number of portals, different approaches have been proposed. Specific portals like double channel cannula 27 or special access system, 28,29 may allow entry of several instruments, or of instruments plus laparoscope.…”
Section: Introductionmentioning
confidence: 99%
“…24 In laparoscopy, reduction of surgical trauma is achieved through a decrease either in the number or size of portals. 25,26 To reduce the number of portals, different approaches have been proposed. Specific portals like double channel cannula 27 or special access system, 28,29 may allow entry of several instruments, or of instruments plus laparoscope.…”
Section: Introductionmentioning
confidence: 99%
“…For adnexal surgery, two-port laparoscopy was first introduced and shown to be safe and feasible by Ghezzi et al [8]. The first port is for the camera, and is introduced through the umbilicus; the second port is a working port and is inserted in the suprapubic area through a Z-tract for a quasiscarless surgical procedure [8].…”
mentioning
confidence: 99%
“…Kalloo et al [8] first reported transvisceral endoscopic surgery through the stomach wall in 2004. Embryonic natural orifice transumbilical endoscopic surgery (E-NOTES) is an approach through the umbilicus that is patent during the embryonic and fetal periods.…”
mentioning
confidence: 99%
“…This represents a further refinement of a previously described two-trocar approach for adnexal surgery 7 that eliminates the need of an extragrasping forceps (and therefore of an ancillary trocar) during salpingectomy. The use of a percutaneous sling has been also described to retract the gallbladder in two-port laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The bag is rolled, grasped with a grasping forceps and introduced through the umbilical port with the free end of the thread held outside the abdomen, as previously described. 7 The fallopian tube, retracted by the transabdominal suture, is then easily placed into the retrieval bag (Fig. 1).…”
Section: Techniquementioning
confidence: 99%